Analytical magnetic field prediction of flux switching machine with segmental rotor. Issue 1 (16th November 2018) - Yang, Yubo; Chen, Jian; Yan, Bo; Zhu, Changqing; Wang, Xiuhe
Abstract : To deeply study the segmental rotor flux switching machine (SRFSM), an analytical subdomain model is first developed to achieve the magnetic field distribution and electromagnetic performance such as back‐electromotive force (EMF), cogging torque, electromagnetic torque, unbalanced magnetic pull, and eddy current losses in the permanent magnet (PM) and rotor support. Then, the number of rotor segments is determined according to the magnetic field modulation theory, and the effect of rotor segment number on the amplitude and total harmonic distortion of speed‐normalised back‐EMF is investigated as well. Using the proposed analytical model, the magnetic field regulation capacity and PM demagnetisation withstand capacity of the series and parallel hybrid excited SRFSMs are investigated and compared. The PM and parallel hybrid excited SRFSM prototype machines with 12 stator slots and 7 rotor segments are manufactured and tested to validate the proposed analytical model.